Large Dust Aerosol Sizes Seen During the 2018 Martian Global Dust Event by the Curiosity Rover - M. T. Lemmon; S. D. Guzewich; T. McConnochie; A. deVicente‐Retortillo; G. Martínez; Michael D. Smith; J. F. Bell III; D. Wellington; S. Jacob (Geophysical Research Letters)
Abstract Mars' atmosphere typically supports dust aerosol with an effective radius near 1.5 μm, varying from ~1 μm during low dust times near northern summer solstice to ~2 μm during higher dust times in southern spring and summer. After global dust events, size variations outside this range have not previously been observed. We report on imaging and spectral observations by the Curiosity rover through the 2018 global dust event. These observations show that the dust effective radius was seasonally normal prior to the local onset of increased opacity, increased rapidly above 4 μm with increasing opacity, remained above 3 μm over a period of ~50 Martian solar days, then returned to seasonal values before the opacity did so. This demonstrates lifting and regional‐scale transport of a dust population ~3 times the size of typical dust aerosol.